Pengaruh Project Based Learning (PJBL) Berbantuan Canva dan Pemberian Reward terhadap Hasil Belajar Siswa pada Penggunaan Mesin Komunikasi Kantor di Kelas XI OTKP SMK Swasta Budisatrya Medan T.A 2024/2025 - Pakpahan, Yolanda Desi Dameria Br.; Simanullang, Rotua SP (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model assisted by Canva and the use of rewards on students’ learning outcomes in the Office Communication Equipment subject for Grade XI OTKP students at SMK Swasta Budi Satrya Medan in the 2024/2025 academic year. The research used a quantitative method with a one-group pretest-posttest design. The sample consisted of one purposively selected XI OTKP class. Data were collected through pretest and posttest assessments. Based on statistical analysis and hypothesis testing using the Paired Sample t-Test, the results showed a significance value (2-tailed) of 0.001 < 0.05 and a t-value of -7.733, indicating a significant difference between pretest and posttest scores. Students’ average scores increased from 45.71 to 88.57 after the implementation of the learning model. Therefore, it can be concluded that the use of PjBL assisted by Canva and rewards has a meaningful and positive impact on students’ academic achievement. The research hypothesis is accepted.